2019
DOI: 10.1016/j.joco.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subthreshold diode micropulse laser photocoagulation on treating patients with refractory diabetic macular edema

Abstract: Purpose To evaluate the effects of subthreshold diode micropulse laser photocoagulation on treating patients with refractory diabetic macular edema (DME). Methods This randomized clinical trial recruited patients with DME in both eyes that were resistant to treatment with intravitreal bevacizumab (IVB). The eyes were randomly divided into two groups who received laser therapy and IVB, or IVB alone. Subthreshold diode micropulse laser photocoagulation and IVB injection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 25 publications
(24 reference statements)
2
16
0
Order By: Relevance
“…Another noteworthy result is that, over the course of the follow-up period, no patients required intravitreal therapy. This confirms the previously reported potential for SMPL to control intraretinal fluid and alleviate the burden of intravitreal treatments [ 4 , 34 , 35 ]; SMPL was effective in keeping retinal thickness under control, stabilizing macular retinal homeostasis. A recent study has shown that visual acuity (in term of loss of five or more ETDRS letters) is not significantly different among eyes initially managed with intravitreal aflibercept, laser photocoagulation or observation at 2 years’ follow-up, in patients with good visual acuity (>79 ETDRS score) at baseline [ 36 ].…”
Section: Discussionsupporting
confidence: 90%
“…Another noteworthy result is that, over the course of the follow-up period, no patients required intravitreal therapy. This confirms the previously reported potential for SMPL to control intraretinal fluid and alleviate the burden of intravitreal treatments [ 4 , 34 , 35 ]; SMPL was effective in keeping retinal thickness under control, stabilizing macular retinal homeostasis. A recent study has shown that visual acuity (in term of loss of five or more ETDRS letters) is not significantly different among eyes initially managed with intravitreal aflibercept, laser photocoagulation or observation at 2 years’ follow-up, in patients with good visual acuity (>79 ETDRS score) at baseline [ 36 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our study did not demonstrate any clinically significant difference (despite the statistical difference in the treatment-naïve group at 12 weeks) in CMT (mean ± SD: −30 ± 125 and −12 ± 128 µm in the treatment-naïve and refractory groups, respectively; p = 0.011 and p = 0.34), thickness area, and macular volume at 3 months and between the groups, which is very similar to many studies. 22,24,29–35,3739 Although, by now, we know that an anatomical reduction of macular edema is not always followed by an improvement in visual acuity, the relationship between these two variables is weak. 40 On the contrary, few reports showed a more important visual and anatomic response, 25,29 but some of them did not use micropulse laser as a monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…40 On the contrary, few reports showed a more important visual and anatomic response, 25,29 but some of them did not use micropulse laser as a monotherapy. 36,41…”
Section: Discussionmentioning
confidence: 99%
“…In the only study evaluating micropulse laser in anti-VEGF-resistant DME, 21 patients had one eye randomly assigned to micropulse laser with intravitreal anti-VEGF and the other eye treated with anti-VEGF monotherapy. At three months, visual acuity decreased significantly in the anti-VEGF monotherapy group (20/100 to 20/123) and increased significantly in the combination group (20/129 to 20/83) [ 143 ]. This therapy is a relatively recent advancement; hence, there is only limited research and long-term outcomes are unclear.…”
Section: Diabetic Retinopathy and Diabetic Macular Edemamentioning
confidence: 99%